2023
DOI: 10.1007/s10113-022-02024-9
|View full text |Cite|
|
Sign up to set email alerts
|

The vegetation cover dynamics and potential drivers of habitat change over 30 years in the Free State National Botanical Garden, South Africa

Abstract: As a conservation strategy, the South African National Biodiversity Institute (SANBI) establishes biodiversity gardens in areas with unique vegetation types that are vulnerable to extinction. The study aimed to (1) determine the vegetation cover dynamics of the Free State National Botanical Garden (FSNBG) over a 30-year period (1987–2017), focusing on different vegetation classes; (2) evaluate the ecological integrity of the Critical Biodiversity Area 1 (CBA1) vegetation using species abundance and vegetation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 106 publications
1
11
0
Order By: Relevance
“…The NDVI value ranges between −1.0 and +1.0, and reflects the health of plants (greens). An NDVI value of 0.6 to 1 represents dense vegetation cover, 0.4 to 0.6 represents moderate vegetation cover, 0.2 to 0.4 represents sparse vegetation cover, 0.1 to 0.2 shows grass cover with bare space, and −1 to 0.1 represents no vegetation, i.e., water cover [88].…”
Section: Discussionmentioning
confidence: 99%
“…The NDVI value ranges between −1.0 and +1.0, and reflects the health of plants (greens). An NDVI value of 0.6 to 1 represents dense vegetation cover, 0.4 to 0.6 represents moderate vegetation cover, 0.2 to 0.4 represents sparse vegetation cover, 0.1 to 0.2 shows grass cover with bare space, and −1 to 0.1 represents no vegetation, i.e., water cover [88].…”
Section: Discussionmentioning
confidence: 99%
“…Two large priority surfaces targeted for rehabilitation at Letšeng Diamond Mine comprise the coarse and fine kimberlite tailings facilities. There is generally limited information and understanding of the establishment of vegetation in grasslands that have undergone severe disturbance (Vukeya et al., 2023 ). These shortcomings fail to achieve the desired rangeland use in the Lesotho Drakensberg.…”
Section: Introductionmentioning
confidence: 99%
“…Grasslands are threatened by fragmentation, which involves the splitting of natural habitats into smaller isolated patches primarily by human disturbances such as land clearing for human settlement (Bredenkamp et al, 2006 ; Carbutt & Kirkman, 2022 ; Matsika, 2008 ; Neke & du Plessis, 2004 ; Skowno et al, 2019 ; Vukeya et al, 2023 ), agricultural activities (Matsika, 2008 ; Nkuekam et al, 2018 ; Turpie et al, 2007 ), and mining activities (Brown & du Preez, 2014 ; Olivier, 2020 ). Several studies have reported that 40% of the grassland biome has been irrevocably modified while 60% of remaining grassland areas are threatened as they are losing an important aspect of their composition, structure, and function (Little et al, 2015 ; Neke & du Plessis, 2004 ; SANBI, 2013 ; Skowno et al, 2019 ), which may need urgent restoration for biodiversity conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that 40% of the grassland biome has been irrevocably modified while 60% of remaining grassland areas are threatened as they are losing an important aspect of their composition, structure, and function (Little et al, 2015 ; Neke & du Plessis, 2004 ; SANBI, 2013 ; Skowno et al, 2019 ), which may need urgent restoration for biodiversity conservation. In South Africa, the continuous habitat fragmentation is likely to increase biodiversity loss (Mullu, 2016 ), particularly for the critically endangered grassland biome species (Brown & du Preez, 2014 ; Matsika, 2008 ; Turpie et al, 2007 ; Vukeya et al, 2021 ); for example, this is observed in the southern Drakensberg Grassland (Turpie et al, 2007 ), and Bloemfontein Karroid Shrubland conserved in the Free State National Botanical Garden (Vukeya et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation